THE IMPACT OF ADMINISTRATIVE CASE MANAGEMENT ON HOSPITAL OPERATIONAL EFFECTIVENESS: A QUALITATIVE CASE STUDY - Vivi Amastasya Sitohang; Ermi Girsang; Sri Lestari Ramadhani Nasution (Pusat Studi Gender dan Anak, 2026)
Effective hospital care is determined not only by clinical factors but also by the efficiency of administrative processes that support the smooth flow of patient care. Administrative issues such as delays in the discharge process, incomplete medical records, and challenges with BPJS claims can impact the quality of care and the hospital’s efficiency. This study aims to analyze the role of Case Managers in improving the effectiveness of hospital services from an administrative perspective at Murni Teguh Hospital in Medan. This study employs a qualitative method with a descriptive approach. Data collection was conducted through in-depth interviews, observations, and document analysis involving eight informants, comprising Case Managers, RMD Coordinators, and the Head of Medical Records. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions using triangulation techniques to ensure the validity of the findings. The results of the study indicate that Case Managers play a strategic role in controlling length of stay (LOS), coordinating with the attending physician (DPJP) and other healthcare personnel, ensuring the completeness of medical records, and facilitating the smooth processing of BPJS claims. In the administrative aspect, the Case Manager serves as a liaison between units to minimize barriers that arise in the service delivery process. Challenges faced include a high patient-to-staff ratio, time constraints, and interprofessional communication barriers. However, through effective communication, intensive coordination, and continuous monitoring, Case Managers contribute to expediting administrative processes, improving documentation completeness, and reducing the potential for pending or rejected claims. The conclusion of this study confirms that the role of the Case Manager contributes significantly to improving the effectiveness of hospital services from an administrative perspective. Optimizing the number of Case Managers and strengthening their functions is recommended as a strategy to improve the quality of hospital administrative management on an ongoing basis.